IMPLIKASI KERJA SAMA INDONESIA - SELANDIA BARU DARI TAHUN 2012 DI BIDANG GEOTHERMAL ENERGI TERHADAP KETAHANAN ENERGI DI INDONESIA - Briando Tanri, (2023)
This study analyzes bilateral cooperation between Indonesia and New Zealand in the field of geothermal energy for national energy security. This study aims to determine the extent of the impact of the cooperation between the two countries on geothermal development in Indonesia. The research uses the theory of international cooperation, the concept of energy transition, and energy security as an analysis framework. Qualitative methods are used by collecting primary data through interviews and secondary data through literature studies. The research sample was selected using purposive sampling. The results of the study show that the potential for geothermal energy in Indonesia has not been utilized optimally due to various inhibiting factors. Bilateral cooperation with New Zealand since 2012 has been considered effective in increasing Indonesia's understanding of geothermal energy. However, this collaboration is not enough to overcome all the inhibiting factors in the development of geothermal energy in Indonesia. This research also examines the role of geothermal energy as renewable energy in achieving national energy security. It was found that with the characteristics and potential of geothermal resources in Indonesia, this energy could be a future solution for energy security, provided all the inhibiting factors can be properly addressed.